PERILAKU MAKAN SIAP SAJI (FAST FOOD) DAN KEJADIAN OBESITAS PADA REMAJA PUTRI DI SMA NEGERI 1 BARUMUN KECAMATAN BARUMUN KABUPATEN PADANG LAWAS TAHUN 2014 - Romaito Hasibuan; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Fast food is characterized by unbalanced nutrient content. mostly high in calories, fat, but very low in fiber. consumption of fast food will lead to excessive problems of nutrition. This research was conducted to study the behavior (knowledge and attitude) of female adolescent and the diet of fast food (frequency, type, and number of carbohydrate, protein, fat and fiber) to the female adolescent at SMAN 1 Barumun. This research is descriptive study by cross sectional study.sample amounted to 77 is the  female student in class X, XI, XII, SMAN 1 Barumun. primary data collection using questionnaires, forms meal frequency and recall 24 hours. The result of research indicates that the female adolescent have good knowledge (97,4%) and have good attitude (74%) to the fast food, type of fast food consumed by adolescent is snack , fried, sausage, and instan noodles with frequency of weekly, daily, weekly, and monthly. Contribution of carbohydrates, proteins and fats consumed by adolescent SMAN 1 Barumun already exceed the recommended dietary allowance figures, while the fiber is still far from the recommended dietary allowance. It suggested of the female adolescent to have a good diet pattern and minimize the consumtion of fast food to avoid the obesity. Keyword : fast food behavior, nutrition status.